Measurement of water vapor content in the polar stratosphere: Syowa Station (69゜00'S, 39゜35'E), spring 1983 - Iwasaka, Yasunobu; Ono, Akira; Saitoh, Sadamu (1985)
P(論文) Water vapor content was measured by a balloon-borne hygrometer (Lyman-alpha/OH fluorescence type) at Syowa Station (69°00'S, 39°35'E), Antarctica on October 27,1983. The result showed a very dry air of about 1 ppmv just above the tropopause. This may be a consequence of the active "freeze-out" of water from the Antarctic stratosphere because of its coldness in winter. departmental bulletin paper